Continuity of care in the Health Care Network: negotiation between users and professionals - Maria Denise Schimith; Ana Cristina Passarella Brêtas; Maria de Lourdes Denardin Budó; Bruna Sodré Simon; Tifany Colomé Leal; Dirce Maria Backes (Rev Rene)
This study aimed to identify the negotiation and shared decision-making between professionals and users in a Family Health Unit and its influence on the continuity of care in the Health Care Network. Qualitative research created from a case study. One conducted 19 interviews, observation and document research. It was developed in a city in the countryside of Rio Grande do Sul, Brazil, in 2012. The results show that decisions used to happen unilaterally and that users and professionals looked for alternative ways to the continuity of care. It was not possible to identify the negotiation between professional and users and it was noticed that the user was alone looking for access. It is understood that primary care in the city researched needs to take responsibility for users and their access.